2015
DOI: 10.1179/1743284715y.0000000056
|View full text |Cite
|
Sign up to set email alerts
|

Electric current pulse induced grain refinement in pure aluminium

Abstract: In the present work, pure aluminium melt was treated using electric current pulse. The effect of current density on the solidification microstructure was investigated by means of wire netting technology. It was found that wire netting could not only effectively stop crystal nucleus to enter other zones but also has relatively small effects on the heat transfer and convection in melts. Theoretical analysis and ANSYS simulation suggested that variation of current density in different localised zones is a key fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…To solve this problem, some refiners and preparation methods are employed to improve the wettability of ceramic particles in the matrix so that they can be uniformly dispersed in the matrix. Some techniques such as ultrasonic stirring technology, electric current pulse and equal channel angular pressing can promote the uniform dispersion of ceramic nanoparticles in aluminium alloys [5,6,17,18]. Li et al [19] developed new mixture heterogeneous nucleants to refine aluminium-based composites.…”
Section: Introductionmentioning
confidence: 99%
“…To solve this problem, some refiners and preparation methods are employed to improve the wettability of ceramic particles in the matrix so that they can be uniformly dispersed in the matrix. Some techniques such as ultrasonic stirring technology, electric current pulse and equal channel angular pressing can promote the uniform dispersion of ceramic nanoparticles in aluminium alloys [5,6,17,18]. Li et al [19] developed new mixture heterogeneous nucleants to refine aluminium-based composites.…”
Section: Introductionmentioning
confidence: 99%
“…In 1966, Utech and Flemings [2] first applied a direct current magnetic field to the solidification process of an In-Sb melt containing Te impurities. In 1995, Bamak et al found that the pulse current greatly reduced the eutectic cells of Sn-Pb alloy [3][4][5][6][7]. In recent years, pulsed electromagnetic field has become an emerging technology in the area of electromagnetic coagulation [4,[8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%